Unlocking EU law - Storey, Tony (Law teacher); Turner, Chris (Barrister) (Abingdon, Oxon : Hodder Education, 2011)
The 'Unlocking the Law' series contains features and activities for undergraduates demonstrating the purpose of different areas of study within the course. The series also covers all the core subjects required by the Bar Council and the Law Society for entry onto professional qualifications.
Includes bibliographical references and index.
Keywords: Law -- European Union countries